(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Due to the rising fuel prices, there is a global shift towards the adoption of hybrid electric vehicles (HEVs) because of their environmental benefits, lower maintenance needs, and alignment with green technology. In HEVs, the energy management system (EMS) is crucial for ensuring efficient energy storage and managing the power flow between the different energy sources, such as the internal combustion engine, battery, and electric motor. The EMS optimizes energy usage, enhances overall vehicle efficiency, and contributes to reducing fuel consumption and emissions, playing a pivotal role in the performance and sustainability of HEVs. This research work proposes an electric vehicle concept powered by multiple energy sources. The design will integrate solar photovoltaic (PV) energy, wind turbine and a fuel cell (FC), (PV + FC) to generate electrical energy. The vehicle will incorporate onboard solar panels, wind energy systems, proton exchange membrane (PEM) fuel cell and supercapacitor units to ensure uninterrupted energy supply during operation which can be achieved with fuzzy-based EMS. Poor design of the EMS will have effect on the performance limitations of the battery state of charge (SOC), and not fully optimizing energy recovery during braking will result in lower overall energy efficiency. This work addresses the above challenges by using fuzzy-EMS. The Simulation results showcase the system’s ability to achieve zero emissions, reduce operational costs, and promote environmental sustainability.